”Memes uden mål”: Hito Steyerl og kunststrejken 2.0 - Routhier, Dominique (K&K - Kultur og Klasse, 2023)
Beginning from a major retrospective exhibition at the prestigious Centre Pompidou in Paris in the summer of 2021, this article discusses the German artist-theorist Hito Steyerl’s political aesthetics and, more specifically, the idea of the art strike as a strategy of resistance. Through a historically contextualizing analysis of two key artworks, Strike I (2010) and Strike II (2012), the article argues that the proper theoretical framework for understanding Steyerl’s work is not post-Occupy “strike art” but rather the cultural logic of the “era of riots.” Thus, the article claims that Steyerl’s art strike resonates in form and content with extra-institutional and “memetic” forms of contemporary protest culture.